Djibouti : Technical Assistance Report-External Sector Statistics. - International Monetary Fund. Statistics Dept. (Washington, D.C. : International Monetary Fund, 2021)
An external sector statistics (ESS) mission visited Djibouti from January 26-30, 2020. This was the fourth mission under the JSA/AFR project to improve ESS in 17 Francophone African countries. The mission found that significant data on direct investment (DI) have not been incorporated in either the balance of payments or international investment position (IIP) statistics since 2017.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet